An Analysis of The Role of Innovation and Digitalization in Enchancing Corporate Competitive Adventage in the Digital Economy Era - Samsul Anwar (PT. Anagata Sembagi Education, 2025)
The rapid advancement of digital technologies has transformed the competitive dynamics of global business, compelling firms to strategically integrate innovation and digitalization to sustain long-term growth. This study aims to analyze the role of innovation and digitalization in enhancing corporate competitive advantage within the digital economy era. Employing a qualitative descriptive design through a systematic literature review (SLR), the research examined 25 peer-reviewed articles published between 2020 and 2025 sourced from Scopus, Web of Science, and Google Scholar. Data were collected and filtered using PRISMA guidelines and analyzed thematically to identify recurring patterns and emerging insights. The findings indicate that innovation is a critical source of differentiation, enabling firms to create unique products, services, and business models, while digitalization strengthens efficiency, agility, and customer engagement. Moreover, the synergy between innovation and digitalization provides dynamic capabilities that allow firms to anticipate market changes and respond proactively. The discussion highlights that organizations integrating both elements outperform those adopting them separately, and that failing to embrace digital innovation increases the risk of market irrelevance.In conclusion, the study affirms that innovation and digitalization are complementary strategic levers that collectively sustain corporate competitiveness in the digital economy. This research contributes by bridging theoretical gaps and offering practical implications for firms across industries.